Gender–age interaction in incidence rates of childhood emotional disorders. Issue 4 (11th August 2014) - Wesselhoeft, R.; Pedersen, C. B.; Mortensen, P. B.; Mors, O.; Bilenberg, N.
Abstract : Background: The post-pubertal association of female gender with emotional disorder is a robust finding. However, studies exploring the association of gender and emotional disorders before puberty are few and present diverging results. The aim of this study was to present gender-specific incidence rates of emotional disorders throughout childhood. Method: This is a population-based cohort study of 907 806 Danish 3- to 18-year-olds. The outcome was assignment of an emotional disorder diagnosis based on in-patient and out-patient data from The Danish Psychiatric Central Register. Outcome measures were incidence rates and cumulative incidences for unipolar depressive disorder (ICD-10: F32–F33), anxiety disorders (ICD-10: F40–F42), and emotional disorders with onset specific to childhood (ICD-10: F93). Results: Pre-pubertal incidence rates for depressive and anxiety disorders were higher for boys than girls. At age 12 years the pattern reversed. The cumulative incidence for any emotional disorder (F32–F33, F40–F42, F93) on the 11th birthday was 0.52% (95% CI 0.50–0.55) for boys and 0.31% (95% CI 0.29–0.33) for girls. On the 19th birthday cumulative incidence was 2.33% (95% CI 2.24–2.43) for boys and 3.77% (95% CI 3.64–3.90) for girls. The pre-pubertal male preponderance was also significant for depressive disorders (F32–F33, p = 0.00144) and anxiety disorders (F40–F42, F93, p < 0.00001) separately. Conclusions: Emotional disorders seem to display a male preponderance before the age of 12 years and a female preponderance thereafter. Studies exploring this gender–age interaction are needed. Still, the results question the general assumption that females throughout the lifespan are more at risk for emotional disorders than males.